Thailand's Position on the International Code of Marketing of Breast-Milk Substitutes: An Overview - Wungrath, Jukkrit (Journal of Child Science, 2023)
The International Code of Marketing of Breast-Milk Substitutes aims to regulate marketing practices of breast milk substitutes to protect breastfeeding. The Code was introduced due to the negative impact of aggressive marketing and promotion of breast milk substitutes on breastfeeding rates, which provide essential nutrients and health benefits for both infants and mothers. Key provisions of the Code, such as banning advertising and promotion to the general public and ensuring accurate information from manufacturers, help reduce the influence of marketing on infant feeding choices. Many countries have adopted and implemented the Code's guidelines, resulting in increased awareness and reduced promotion of breast milk substitutes. However, challenges remain in effective implementation and enforcement, and breastfeeding rates still vary globally. Thailand supports the Code and has implemented its guidelines into national legislation. The country has established laws to restrict promotion and advertising of breast milk substitutes and initiatives to promote and support breastfeeding, such as the Baby-Friendly Hospital Initiative. However, challenges in enforcing the guidelines and varying breastfeeding rates remain. Thailand is working towards improving implementation and enforcement of the guidelines and promoting breastfeeding practices in the country.
Keywords: the international code; marketing; breast milk substitutes